Comparative analysis of electrical and thermal control of the lining state of induction apparatus of copper wire manufacture - Zolotaryov, V.M.; Shcherba, M.A.; Belyanin, R.V.; Mygushchenko, R.P.; Kropachek, O.Yu. (Електротехніка і електромеханіка, 2018)
Aim. This article is intended to develop a technique for monitoring the lining state of induction channel furnaces for melting
oxygen-free copper by monitoring changes in the distribution of thermal fields in their lining and carrying out a comparative
analysis of the developed technique with the existing one that controls the electrical resistance of the melting channel of the
furnaces. Technique. For carrying out the research, the theories of electromagnetic field, thermodynamics, mathematical physics,
mathematical modeling based on the finite element method were used. Results. A technique for diagnosing the lining state of the
induction channel furnaces for melting oxygen-free copper has been developed, which makes it possible to determine the
dislocation and the size of the liquid metal leaks by analyzing the temperature distribution over the body surface both the inductor
and the furnace. Scientific novelty. The connection between the temperature field distribution on the surface of the furnace body
and the dislocation and dimensions of the liquid metal leaks in its lining is determined for the first time. Practical significance.
Using the proposed technique will allow to conduct more accurate diagnostics of the lining conditions of the induction channel
furnaces, as well as to determine the location and size of the liquid metal leaks, creating the basis for predicting the working life
of the furnace Цель. Целью статьи является разработка методики контроля состояния футеровки индукционных канальных печей
для плавки бескислородной меди путем мониторинга изменений распределения тепловых полей в их футеровке и
проведение сравнительного анализа разработанной методики с существующей, которая контролирует
электрическое сопротивление плавильного канала печей. Методика. Для проведения исследований использовались
положения теории электромагнитного поля, термодинамики, математической физики, математического
моделирования с применением метода конечных элементов. Результаты. Разработана методика диагностики
состояния футеровки индукционной канальной печи для плавки бескислородной меди, которая позволяет определять
дислокацию и размер протеканий жидкого металла путем анализа распределения температуры по поверхности
корпуса индуктора и печи. Научная новизна. Впервые установлена связь между распределением температурного поля
на поверхности корпуса печи и дислокацией и размерами протеканий жидкого металла в ее футеровке. Практическое
значение. Использование предложенной методики позволит проводить более точную диагностику состояния
футеровки индукционных канальных печей, а также определять расположение и размеры протеканий жидкого
металла, создавая основы для прогнозирования ресурса работы печи